The Mechanisms and Quality Markers of Anti-rheumatoid Arthritis of Traditional Chinese Medicine - Adu, Mozili; Qiu, Yongwei; Ma, Qinge; Zhong, Guoyue; Guo, Jia-Zeng; Wei, Rongrui (Combinatorial Chemistry & High Throughput Screening, 2025)
BackgroundRA is a recurrent autoimmune disease that has significant adverse effects on the physical and mental health of patients. Traditional Chinese medicine has shown significant advantages in the prevention and treatment of RA. Numerous clinical and experimental studies have confirmed that traditional Chinese medicine components have clear therapeutic effects and minimal adverse reactions in treating RA. The research on traditional Chinese medicine for the prevention and treatment of RA has become a hot topic in the field of autoimmune diseases.MethodsThe related references about the mechanisms and Q-markers of anti-RA of traditional Chinese medicine in this review were collected from Willy, SpringLink, Web of Science, Elsevier, PubMed, SciFinder, Scopus, ACS publications, Baidu Scholar, Google Scholar, and CNKI.ResultsThe traditional Chinese medicine components such as terpenoids, flavonoids, and alkaloids have significant anti-RA effects, and their mechanisms are mainly to inhibit NF-κB signaling pathway, inhibit the proliferation of RA fibroblasts like synovial cells, and regulate Th1/Th2 cell balance, and so on. Predicting and studying the Q-markers of traditional Chinese medicine anti-RA by plant phylogeny and chemical componentss, traditional medicinal properties, pharmacokinetics, component measurability, correlation between composition and efficacy, and gut microbiota will provide scientific foundations for the research and further development of anti-RA traditional Chinese medicine.ConclusionThe active components of traditional Chinese medicine exhibited the characteristic of multiple mechanisms in the treatment of RA, such as terpenoids had anti-angiogenesis effects, flavonoids had anti-inflammatory and cartilage protective effects, and alkaloids had anti-inflammatory and analgesic effects. The proposal of Q-markers for anti-RA provided new research ideas for promoting the development of new drugs for anti-RA and ensuring the safety and effectiveness of clinical medications.
Keywords: traditional Chinese medicine